Extending ASSL: Making UML Metamodel-based Workflows executable - Brüning, Jens; Hamann, Lars; Wolff, Andreas (Electronic Communications of the EASST, 2011)
ASSL is a language that enables UML developers to test and certify UML and OCL models [5]. Snapshots of system states are semi-automatically created and main parts of the UML action semantics is implemented by the language. Its interpreter is the well-known UML modeling tool USE. The article proposes a number of language extensions to ASSL. These include (sub ) procedure calls and pre- and postcondition checks on entering and exiting of operations using OCL. The paper motivates the need for these extensions as well as their usage and development along the problem of metamodel-based execution of workflow models. Executable workflow models, driven by ASSL procedures, are introduced in detail to present the usage of ASSL and our extensions.